The decolonisation of community development in Haut-Katanga and the Zambian Copperbelt, 1945–1990 - Larmer, M; Taylor, R (James Currey, 2021)
The first comparative historical analysis - local, national and transnational - of the cross-border Central African copperbelt; a key work in studies of labour, urbanisation and African studies.